25.3k views
3 votes
For f(x)=2x+1 and g(x)=x^2-7 find (f-g)(x)

User Eskil
by
5.5k points

1 Answer

3 votes

Answer:

-x² + 2x + 8

Explanation:

Essentially we need to subtract g(x) from f(x):

(f - g)(x) = f(x) - g(x) = (2x + 1) - (x² - 7)

Distribute the negative:

(2x + 1) - x² - (-7) = (2x + 1) - x² + 7

Combine like terms:

2x + 1 - x² + 7

-x² + 2x + 8

Thus, the answer is -x² + 2x + 8.

~ an aesthetics lover

User Letie
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.